PG88 Time to react – return to acute care training. (10th November 2020) - Harrison, Tracey; Horn, Jill; Robinson, David; Jones, Elizabeth; Farrow, Catherine; Atkinson, Phil; Fox, Roshanne
Abstract : Background: Approximately 10% of all medical trainees are taking time away from training due to variety of professional and personal reasons 1 . Returning to training following an episode of absence can be a challenging and stressful time affecting confidence. The aim of this course is to give trainees the confidence to return to acute practice following time away from work. Summary of Work: We have designed a one day course aimed at both junior and senior trainees from all acute specialities; the course consists of both clinical skills refresher training and simulated clinical scenarios. The course has a structured timetable for the day but allows an informal approach to suit the needs of the trainee and enhance the learning both as an individual and as a team. In light of COVID-19, trainees returning to work may experience a heightened sense of anxiety due to the on-going changes to practice. We have developed scenarios incorporating these changes, to allow trainees the opportunity to be 'hands on' and experience these in a safe learning environment. The course concentrates on team working and allows trainees the opportunity to build their confidence in delivering time critical handovers, complex referrals and making challenging decisions whilst in a supportive environment. Trainees are given the opportunity to rehearse the use of PPE and experience the challenges faced whilst wearing this. Summary of Results: Since 2019 a total of 23 trainees have accessed the course from a variety of acute specialties and differing time frames away from work. Evaluation of the course has been extremely positive; 96% of attendees agreed or strongly agreed that they felt the course was relevant to their learning needs. Qualitative feedback includes comments such as 'excellent' 'supportive faculty' and 'made me feel more confident in my return to work'. Discussion, Conclusions and Recommendations: The day is designed to have a flexible approach; this has enabled us to focus our last course on relevant changes to practice as a result of COVID-19. This allowed delivery of up to date information on current clinical practice which helped to further alleviate trainees' anxieties. It is the ethos of the course that, by taking care of this vulnerable group of doctors, they will return to work well prepared to take care of their patients. We recommend that all trainees are offered this supported learning prior to them returning to the clinical environment.